Burn out de Mehdi Meklat et Badoudine Saïd Abdallah: variation romanesque d'un fait divers tragique - Almeida, José Domingues de (2018)
The novel Burn out (2015), published by two young bloggers from neighbourhoods at risk and from two different communities - Mehi Meklat and Badroudine Saïd Abdallah - draws its title from an Anglicism combining depression and fire, and is inspired by a tragic fait divers: Jamal Chaars immolation on February 13, 2013 in front of the Pôle Emploi agency in Nantes Est following an administrative refusal of his unemployment application. The evocation of this drama allows the authors to engage in a fierce and dark fictional narrative, but raises the great societal issues of multicultural France. We propose to analyse the mechanisms of this fait divers fictional reworking.